181k views
1 vote
An arithmetic sequence is defined by the recursive formula t1 = 11, tn = tn - 1 - 13, where n ∈N and n > 1. Which of these is the general term of the sequence? A) tn = 11 - 13(n - 1), where n ∈N and n > 1 B) tn = 11 - 13(n - 2), where n ∈N and n ≥ 1 C) tn = 11 - 13(n - 1), where n ∈N and n ≥ 1 D) tn = 11 - 13(n + 1), where n ∈N and n ≥ 1

User Karamjit
by
6.2k points

1 Answer

4 votes
ANSWER

The general term of the sequence is.


t_n= 11 - 13(n - 1)

The correct answer is C.

Step-by-step explanation
The recursive definition of the sequence is given by


t_n=t_(n-1)-13
where

t_1=11

and

n > 1.

When we plug in

n = 2
into the recursive definition, we obtain,


t_2=t_(2-1)-13



\Rightarrow t_2=t_(1)-13


\Rightarrow \: t_2=11-13


t_2= - 2

The Commons difference is

d = - 2 - 11 = - 13

The general term is given by the formula,


t_n= t_1 + (n - 1)d

We substitute the above values to obtain,


t_n= 11 + (n - 1)( - 13)

This implies that,


t_n= 11 - 13(n - 1)

where,

n\in N
User Ryan Amaral
by
5.7k points